UJI ANTIBAKTERI EKSTRAK BATANG GAHARU (Aquilaria malaccensis) BERBASIS KOLIN KLORIDA:ASAM SITRAT TERHADAP Bacillus cereus dan Shigella dysenteriae - Hasan, Nahrul; Marlina, Sri; Amelia, Ayu; Syahputra, Ghalib Syukrillah; Sari, Diani Mega (Jurnal Buana Farma, 2025)
Infections caused by Bacillus cereus and Shigella dysenteriae are serious health problems as they can lead to gastrointestinal disorders and contribute to the emergence of antibiotic resistance. One potential strategy to overcome this challenge is the discovery of new antibacterial agents derived from natural sources, such as agarwood (Aquilaria malaccensis). This study aimed to evaluate the antibacterial activity of gaharu stem extract using a Natural Deep Eutectic Solvent (NADES) composed of choline chloride and citric acid through the Ultrasound Assisted Extraction (UAE) method. The antibacterial assay was performed using the disc diffusion method with various NADES ratios (1:1, 2:1, 1:2, 1:3, 1:4, and 4:1 g/g), with chloramphenicol as the positive control and 10% DMSO as the negative control. The results indicated that the NADES extract with a 1:4 g/g ratio produced the largest inhibition zones against Bacillus cereus and Shigella dysenteriae. Moreover, the Minimum Inhibitory Concentration (MIC) test showed that the 1:4 NADES extract effectively inhibited bacterial growth at a concentration of 30%. These findings suggest that gaharu stem extract prepared with NADES is a promising, eco-friendly, and potent antibacterial agent.